Association Between BRCA1 Expression Status and Lymph Node Status in Breast Cancer Patients in NTB - Wikananda, Ida Bagus Wisnu; Lestari, Rizka Vidya; Djannah, Fathul (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Breast cancer is the most common type of cancer among women in Indonesia, with incidence and mortality rates continuing to rise. One important factor in the development of this disease is the involvement of BRCA1 gene expression. Disruption of BRCA1 gene function plays a role in tumorigenesis. In addition, axillary lymph node status is an important prognostic factor that determines disease stage and progression. However, the relationship between BRCA1 expression and lymph node involvement is still inconsistent, requiring further research to clarify its association. This study aimed to determine the relationship between BRCA1 expression and lymph node status in breast cancer. This research was an analytical observational study with a cross-sectional design. BRCA1 expression was assessed using the H-Score method and classified into high expression (H-Score >100) and low expression (H-Score ≤100). Lymph node status was categorized as negative (N−) or positive (N+). Data from 42 breast cancer samples were analyzed using the Chi-Square test. The results showed that 19 patients (45.2%) had low BRCA1 expression, while 23 patients (54.8%) had high BRCA1 expression. Based on lymph node status, 12 patients (28.6%) were classified as N− and 30 patients (71.4%) as N+. Statistical analysis demonstrated no significant association between BRCA1 expression and lymph node status (p=0.096). In conclusion, BRCA1 expression cannot yet be used as a strong indicator in determining lymph node status in breast cancer patients in NTB.